Peran Kesra sebagai Mitra dalam Program Beasiswa Santri Pondok Pesantren (BSPP) Universitas Al Azhar Kairo Mesir - Andini, Faiza Irisaliya; Reviandani, Oktarizka (VISA: Journal of Vision and Ideas, 2025)
The Al-Azhar University Cairo Islamic Boarding School Santri Scholarship Program (BSPP) is a strategic initiative of the East Java Provincial Government which aims to increase access to higher education and the quality of Islamic boarding school human resources (HR). Despite the positive impact of the programme, some challenges, such as changes in international regulation and the sustainability of the programme, remain important issues. This research aims to analyze the role of the People's Welfare Bureau (Kesra) as the main partner in implementing the BSPP program, especially in supervision, fund management and program evaluation. This research uses a qualitative approach with descriptive methods. Data was collected through in-depth interviews, document studies and observations at research locations, namely the Kesra Office, the Islamic Boarding School and Diniyah Development Institute (LPPD), and partner Islamic boarding schools. The research results show that the BSPP program has had a significant impact in improving the quality of Islamic boarding school human resources in East Java, especially through the transfer of knowledge from graduates of Al-Azhar University in Cairo. Kesra's role as policy initiator and program supervisor proved to be a key factor in the success of this program. In addition, cross-agency collaboration, including the Ministry of Religious Affairs and LPPD, succeeded in increasing transparency and effectiveness in programme implementation. However, challenges such as changes to visa regulations by the Egyptian government require more flexible policy adaptation. The conclusions of this research confirm that the BSPP program succeeded in achieving its initial goals, but required innovation in management and evaluation to ensure sustainability in the future. This research provides recommendations to strengthen technology-based monitoring systems and involve alumni in supporting prospective scholarship recipients.